Perceived neighborhood-level drivers of food insecurity among aging women in the United States: A qualitative study - Shieh, Jacqueline A. (J Acad Nutr Diet, 2021)
BACKGROUND: Aging populations in the United States (US) exhibit high rates of food insecurity and chronic illness. Few studies have explored the neighborhood-level drivers of food insecurity among such populations, and how they intersect with experiences of aging. OBJECTIVE: The aim of this study was to explore how aging women experience food insecurity in the US, and the neighborhood-level factors that influence these experiences. DESIGN: Semi-structured qualitative interviews were conducted to elicit participants’ perceptions of how their neighborhood influenced their experiences with food security and aging. PARTICIPANTS/SETTING: Thirty-eight food-insecure women 50 years and older were purposively sampled from the Northern California, Georgia, and North Carolina sites of the Women’s Interagency Human Immunodeficiency Virus Study (WIHS). Interviews were conducted between November 2017 and July 2018 at the three WIHS sites. ANALYSIS: Three researchers thematically analyzed the data using an inductive-deductive approach. RESULTS: Participants described neighborhood-level drivers of food insecurity that centered around three themes: accessibility of food from traditional food stores, the role of food aid institutions, and the intersection of aging with the food environment. Participants explained that food insecurity was related to limited access to food stores largely due to long distances and poor public transportation in Georgia and North Carolina, and high food prices in Northern California. Most participants described being dependent on food aid programs, but found this difficult due to poor quality food and long wait times. Aging-related issues emerged as a cross-cutting theme, with fatigue, poor strength, and chronic illness amplifying barriers to accessing food. CONCLUSIONS: Findings from this study reveal the structural barriers that aging women face in accessing healthy food within their neighborhoods, and how experiences with aging and chronic illnesses exacerbate these barriers. While future programs should address common neighborhood-level barriers such as the accessibility and affordability of healthy foods, they should also be tailored to aging women and the local context.